A recepção do instituto da adoção no direito civil brasileiro - Juliana Pereira Soares (2012)
This work aims to verify how the institution of adoption was approved in Brazilian civil law. Considering the colonization of Brazil and the formation of the Brazilian state, initially, it contextualizes the legal system covering the history of Portuguese law and the legal treatment given to the adoption in Portugal. Then, it highlights and analyzes the existing rules relating to adoption in Brazil in the period between its political independence and the emergence of its first Civil Code. Later, itaddresses the positioning of Brazilian jurists of the time and, based on records located in the National Public Archives of Rio de Janeiro, it analyzes the practice of adoption in the Brazilian Imperial Court in the second half of the nineteenth century. Finally, the present work studies how the development of the institution of adoption affected the first Brazilian Civil Code.